Pelatihan Merancang dan Melaksanakan Assesmen Diagnostik pada Guruguru SD di Kecamatan Sawan (Educemara: Jurnal Pengabdian Masyarakat, 2024)
The government continues to develop the curriculum in Indonesia as an effort to improve the quality of education in general. The development of this curriculum will of course result in several changes in its elements, both in terms of content standards, processes, and also assessment standards. Assessment in a learning process is certainly important for student success. The place where this community service is carried out is in Sawan District, Buleleng Regency. This activity will be carried out in May – July 2023 by taking training activities on Saturdays. The target subjects in this community service activity are elementary school teachers in Sawan District. The teachers invited were class 1-6 teachers and dapodik operators. The approach method used in this community service activity is by conducting training and mentoring methods. Based on the results of the service that has been carried out, it can be concluded that it is important to have training on diagnostic assessment because in this service only 65% of teachers do not fully understand diagnostic assessment, and 35% do. Teachers who already understand diagnostic assessment are teachers who are part of teacher mobilization activities. The enthusiasm of the teachers in participating in the training was proven by their full attendance and not being absent during the activities. Teachers admit that with the implementation of the independent curriculum they have to learn a lot about assessment, one of which in the independent curriculum assessment is diagnostic assessment. This form of service allows teachers to learn new things about assessments, especially in the independent curriculum. This causes them to always participate in community service activities well and follow directions from lecturers regarding the assignments given.
Keywords: diagnostic assessment, elementary school teacher, Sawan district Buleleng